Amyloid Diseases (IntechOpen, 2023)
Neurodegenerative diseases are severe, rapidly developing, and currently incurable conditions that result in progressive degeneration and the death of neurons. This causes dementia, movement problems, and essentially loss of personal identity. Amyloids attempts to answer the following questions: (1) why do we develop these severe neurodegenerative diseases? (2) what histological and physiological changes are observed upon development and progression of these diseases? and (3) how can we treat amyloid-associated diseases?